Production And Characterization Of Monoclonal Antibodies Against Onchocerca gibsoni - Yudha Fahrimal; Bruce Copeman (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2004)
.